Neutralization and World Politics - Black, Cyril E. (Cyril Edwin), 1915-1989 (Book collections on Project MUSE., 1968)
Neutralization is a technique for the management of power in international relations: for the restraint and, to a degree, regulation of the exercise of power in areas that become focal points of competitive struggle. In this volume four leading scholars assess the potential uses of neutralization in the contemporary world. In interlocking essays the authors discuss the functions of neutralization, relevant historical precedents, preconditions for its establishment, methods of negotiating neutralization, maintenance of neutralization, and the prospects for neutralization in Southeast Asia today. Originally published in 1968. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.